Conceptualizing the Aurora: An Exploration of Performative Understanding through Interactive Art - Jensen, Signe Kjaer; Pop-Tiron, Cristina (Nordlit, 2020)
Aurora – Connecting Senses is a multimodal, interactive art installation which explores the ideas of the Northern Lights through sound, light, colour, and interaction. The installation creates a space where the colours, magic, and mystique of the aurora are brought down to earth and into people’s everyday lives. It is inspired by popular and scientific representations of the real aurora and invites audiences to create yet another interpretation of the natural wonder. In doing so, audiences are also invited to reflect upon the nature of the aurora and on the act of interpretation and exploration. In this article, we provide a thorough description of the ideas and development of the installation, along with photo and video documentation, and offer a critical discussion of the installation as a performative art piece with certain affordances for interaction, performativity, and active reflection. Our discussion is grounded in our observations of audiences engaging with the installation, aspiring to relate the theoretically available affordances for interaction with the differences in observed audience behaviour. The theme and reflective potential of the installation is further compared to other contemporary art pieces dealing with conceptualizations of nature or natural phenomena. By doing this, we aim to use the aurora installation as a stepping stone for addressing the potential of interactive art to highlight or even construct certain understandings of a natural ‘reality’ and for engaging audiences in a further negotiation of these understandings.